SUSTAINABILITY OF EXISTENCE: HOW FIRM DURABILITY INTERACTS WITH FINANCIAL DECISIONS IN DISTRESS PREDICTION MODELS - Eksandy, Arry; Arum, Mega; Sari, Riski Ulan; Ariani, Meiliyah; Zulhawati, Zulhawati (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2025)
existence on financial distress in retail companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Using a quantitative approach with panel data regression, this research examines 22 retail companies selected through purposive sampling, resulting in 110 firm-year observations. Financial distress is measured using the Altman Z-Score, while independent variables include capital structure (Debt to Equity Ratio), operational cash flow ratio, and company existence (age since IDX listing). Data analysis was performed using the Fixed Effect Model in EViews. The results indicate that capital structure has a significant negative effect on financial distress, while company existence shows a significant positive influence. However, operational cash flow does not significantly affect financial distress. Collectively, these three variables explain 93% of financial distress variance in the retail sector. These findings suggest that retail company managers should prioritize optimal capital structure management and recognize that organizational maturity contributes to financial resilience. Investors and regulators can utilize company age as an additional indicator when assessing financial distress risk. This study contributes to financial distress literature by integrating firm durability factors with financial metrics in Indonesia's retail sector, providing empirical evidence on how non-financial factors interact with financial decisions in distress prediction.